Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1080/15513819609168711
|View full text |Cite
|
Sign up to set email alerts
|

Is There Transplacental Transfer of Asbestos? A Study of 40 Stillborn Infants

Abstract: An autopsy study was conducted to investigate whether there is transplacental transfer of asbestos in humans. The asbestos burden of lung, liver, skeletal muscle, and placenta digests of 40 stillborn infants was determined using a bleach digestion method. The fibers detected in the tissue digests were characterized as to the type of asbestos, using electron microscopy, energy-dispersive x-ray analysis, and selected-area diffraction analysis. Placental digests of 45 full-term, liveborn infants were similarly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The lung is particularly likely to retain fibers, since it is one of the first organs to be exposed to the maternal blood carrying the fibers from the placenta, and has a rich capillary network that may trap more fibers. Additionally, in our previous studies, fibers were found in the liver and lung of stillborn infants (Haque et al, 1996.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The lung is particularly likely to retain fibers, since it is one of the first organs to be exposed to the maternal blood carrying the fibers from the placenta, and has a rich capillary network that may trap more fibers. Additionally, in our previous studies, fibers were found in the liver and lung of stillborn infants (Haque et al, 1996.…”
mentioning
confidence: 73%
“…There are reports of childhood mesotheliomas, particularly in children of asbestos workers (Fraire et al, 1988;Cooper et al, 1989). Recent autopsy studies have documented the presence of asbestos, not only in children but also in stillborn infants, with the latter suggesting transplacental transfer of asbestos fibers (Haque et al, 1990(Haque et al, , 1996. The uptake and circulation of asbestos fibers after ingestion and their distribution to various organs have been demonstrated in several adult human as well as animal studies (Carter & Taylor, 1980;Cook & Olson, 1979;Cunningham & Pontefract, 1973;Hallenbeck & Patel-Mandlik, 1979).…”
mentioning
confidence: 99%
“…Tissue digests were characterized as to the type of asbestos using EDXA-EM and selected-area diffraction analysis. Small, thin, uncoated asbestos fibers were found in 15 of the 40 stillborn infants, while no fibers were found in the placental tissue of any live-born controls (Haque et al, 1996). Interestingly, in a larger third study by Haque et al (1998) using the same methods, low numbers of asbestos fibers were also found in 15% of the live-born placental controls.…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 89%
“…An asbestos fiber burden ranging from 71,000 to 357,000 fibers/g wet weight was detected in at least one organ of all five infants (Haque et al, 1992). Haque et al (1996) continued by examining the organs from 40 stillborn infants and comparing them to the placenta from liveborn controls. Tissue digests were characterized as to the type of asbestos using EDXA-EM and selected-area diffraction analysis.…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%
“…In humans, asbestos fibers have been particularly identified in samples of lymphatic ganglions (Dodson et al, 1990;Sebastien et al, 1979), in healthy or diseased parietal pleura (Boutin et al, 1996;Dodson et al, 1990;LeBouffant et al, 1976;Sebastien et al, 1980;Suzuki and Kohyama, 1991;Suzuki et al, 2005), omentum and radix mesenteri (Dodson et al, 2001;Dodson et al, 2000) and in the placenta and tissue samples of stillborn infants (Haque et al, 1996;Haque et al, 1992;Haque et al, 1998).…”
Section: Toxicokinetics-metabolism Of Safs and Tafsmentioning
confidence: 99%